E-Learning in College: Bibliometric Analysis of Virtual Learning Environments and Online Course Delivery - Adi Nugroho Susanto Putro (Eastasouth Institute, 2023)
Electronic Learning, also known as e-learning, has become an integral part of modern education systems, revolutionizing traditional learning practices in higher education. This research paper presents a comprehensive bibliometric analysis of virtual learning environments (VLEs) and online course delivery in higher education. The study involves data collection from reputable academic databases, including Web of Science, Scopus, PubMed, Google Scholar, and institutional repositories. The research methodology includes co-authorship network analysis, journal and conference analysis, citation analysis, and keyword co-occurrence analysis using VOSviewer software. The analysis reveals collaborative patterns among researchers, influential publication outlets, highly cited papers, and emerging research themes in electronic learning. The results offer valuable insights into the evolution of electronic learning research, identifying key contributors, trends, and gaps in the field. This study aims to guide educators, researchers, and policymakers in enhancing electronic learning experiences and shaping the future of education in higher institutions.